The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1111/j.1399-3054.1986.tb01923.x
|View full text |Cite
|
Sign up to set email alerts
|

Histones and the first cell cycle in maize germination

Abstract: E, 1986, Histones and the first cell cycle in maize germination. -Physiol. Plantarum 68: 259-264.The timing of the onset of cell division during seed germination in maize and the role of histones for this process have been studied. Embryonic axes of maize seeds [Zea mays L, hybrid H-30) were incubated in a sterile nutrient medium for different periods of time. For some experiments putresdne was also added, Mesocotyl, root tip and scutellar node were dissected at specific periods after incubation and the mitoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…The mesocotyl was the first and more active tissue showing mitotic figures, followed by seminal and primary root. This result confirms previous findings (Baiza et al 1986).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…The mesocotyl was the first and more active tissue showing mitotic figures, followed by seminal and primary root. This result confirms previous findings (Baiza et al 1986).…”
Section: Resultssupporting
confidence: 94%
“…The first mitotic figures were observed in mesocotyl meristems, about 18 to 22 h after imbibition, followed by seminal and primary roots. These data confirm previous findings (Baiza et al 1986), and validate the use of the in vitro system as a model for further studies. In both systems, cell division is observed as waves of cells entering the process at the periods stated.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Early protein synthesis has been shown to occur prior to, or simultaneously with the initiation of cell division due to stored RNA and transcription (BRAY and SMITH, 1985;DELSENG et al, 1981). In maize germination, histone synthesis is initiated far in advance of the actual onset of cell division (BAIZE et al, 1986). In pea embryos it has been shown that, at the time of DNA synthesis, there is an accumulation of non-histone chromosomal proteins, decrease of H, histone concentration whereas the other 4 histones increase in equimolecular amount with the DNA (GRELLET et al, 1977).…”
Section: Variations Of Content Of Nuclear Proteins During Transition mentioning
confidence: 99%